Effect of Aging on Bond Strength of Two Soft Lining Materials to a Denture Base Polymer - Salloum, Alaa’a M. (J Indian Prosthodont Soc, 2014)
The purpose of this study was evaluation the effect of immersion in distilled water and inorganic artificial saliva on the shear bond strength of a heat-polymerized and an auto-polymerized silicone-based denture lining materials. The denture liners investigated were Molloplast-B (heat-polymerized), and Mollosil plus (auto-polymerized). The soft liner specimens were 10 × 10 × 2.5 mm and were processed between two poly(methylmethacrylate) plates. Thirty shear specimens for each type of test lining material were prepared. Specimens were divided equally into three groups for each test lining material: first group, specimens were tested after 48 h of preparation without immersion; second group, specimens were tested following immersion in distilled water at 37 °C for 12 months; and third group, specimens were tested following immersion in inorganic artificial saliva at 37 °C for 12 months. Shear bond strength was measured using an universal testing machine at a crosshead speed of 40 mm/min and failure mode (adhesive, cohesive and mixed) after debonding was assessed. Data were statistically analyzed with one-way analysis of variance (ANOVA) (α = 0.05). ANOVA was followed by Bonferroni post hoc tests for pairwise comparisons. A significant difference in shear bond strength was detected between Molloplast-B and Mollosil plus following immersion in distilled water and artificial saliva. Molloplast-B demonstrated considerably higher shear strength than Mollosil plus after immersion. Shear strengths of the lining materials investigated reduced significantly after immersion in both solutions. Visual examination after separation revealed that the soft materials tested exhibited mostly adhesive failure. The effect of immersion in distilled water and inorganic artificial saliva on bond strength of test lining materials was perceivable; however, both of them had acceptable bond strength and might be proper for long-term use.